Analysis of multipath routing, part 2 mitigation of the effects of frequently changing network topologies. - Tsirigos, A.
In this paper, we extend the analysis of multipath routing presented in our previous work, so that the basic restrictions on the evaluation and optimization of that scheme can be dropped (e.g., disjoint paths and identical paths in terms of failure probability). In that work, we employed diversity coding in order to provide increased protection against frequent route failures by splitting data packets and distributing them over multiple disjoint paths. Motivated by the high increase in the packet delivery ratio, we study the increase we can achieve through the usage of multiple paths in the general case, where the paths are not necessarily independent and their failure probabilities vary. For this reason, a function that measures the probability of successful transmission is derived as a tight approximation of the evaluation function Psucc. Given the failure probabilities of the available paths and their correlation, we are able to find in polynomial time the set of paths that maximizes the probability of reconstructing the original information at the destination.
Keywords: QoS; Ad hoc networks; Ad hoc routing; Alternate-path routing; Data packets splitting; Diversity coding; Evaluation function; Failure probabilities; Multipath routing; Network topologies; Network-fault tolerance; Optimization; Packet delivery ratio; Polynomial time; Quality of service; Route failures